Chemical Composition and Insecticidal Activity of Essential Oil from Coriandrum sativum Seeds against Tribolium confusum and Callosobruchus maculatus. (25th November 2012) - Khani, Abbas; Rahdari, Tahere
Abstract : The biological activity of essential oil extracted from coriander, Coriandrum sativum L. (Apiaceae), seeds against adults of Tribolium confusum Duval (Coleoptera: Tenebrionidae) and Callosobruchus maculatus F. (Coleoptera: Bruchidae) was investigated in a series of laboratory experiments. Fumigant toxicity was assessed at 27 ± 1 °C and 65 ± 5 % R.H., in dark condition. Dry seeds of the plant were subject to hydrodistillation using a Clevenger-type apparatus. The composition of essential oil was analyzed by gas chromatography mass spectrometry. The predominant components in the oil were linalool (57.57%) and geranyl acetate (15.09%). The mortality of 1–7-day-old adults of the insect pests increased with concentration from 43 to 357  μ L/L air and with exposure time from 3 to 24 h. In the probit analysis, LC50 values (lethal concentration for 50% mortality) showed that C. maculatus (LC50 = 1.34  μ L/L air) was more susceptible than T. confusum (LC50 = 318.02  μ L/L air) to seed essential oil of this plant. The essential oil of C. sativum can play an important role in stored grain protection and reduce the risks associated with the use of synthetic insecticides.